Pelatihan Mitigasi Bencana Gempa Bumi Melalui Pembentukan Kader Santri Siaga Gempa Bumi (SSGB) di Kabupaten Ponorogo - Risma Dwi Arisona; Nastiti Mufidah; Amiruddin Amiruddin (Manhaj: Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
The phenomenon of earthquakes has occurred several times in Ponorogo Regency, although with small strengths. This indicates that there is an active fault in the area surrounding Ponorogo Regency. The results of a survey conducted by researchers show that of the 93 Islamic boarding schools in Ponorogo Regency, none of them have conducted disaster education, especially earthquakes. Based on this, the researchers have the idea to carry out training for Islamic boarding school students in Ponorogo Regency whose members are called the SSGB Cadre (Earthquake Disaster Preparedness Santri). The purpose of this service is to determine the level of knowledge of students in earthquake disaster mitigation, implementation of earthquake disaster mitigation training, and the process of mentoring students for earthquake disaster preparedness (SSGB) in Ponorogo Regency. This community service research method uses Participatory Rural Appraisal (PRA) combined with Participatory Action Research (PAR). In the implementation of this service, there are three expected achievement goals, namely increasing students' knowledge regarding earthquake disasters, implementing disaster mitigation training, and providing assistance to SSGB Cadres. The final conclusion is to increase the knowledge of SSGB cadres by 79%. The satisfaction level of disaster mitigation training is 92%. And the level of achievement of SSGB cadre assistance carried out online by the service team and offline by cadres showed 94%, which means that most of the cadres had carried out follow-up activities related to disaster mitigation training in their respective islamic boarding schools.